1999
DOI: 10.1051/rnd:19990102
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption, blood transport and hepatic and muscle metabolism of fatty acids in preruminant and ruminant animals

Abstract: -Current research on lipid metabolism in ruminants aims to improve the growth and health of the animals and the muscle characteristics associated with meat quality. This review, therefore, focuses on fatty acid (FA) metabolism from absorption to partitioning between tissues and metabolic pathways. In young calves, which were given high-fat milk diets, lipid absorption is delayed because the coagulation of milk caseins results in the retention of dietary fat as an insoluble clot in the abomasum. After weaning, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
23

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 62 publications
3
89
0
23
Order By: Relevance
“…These results are in concordance with a lower rate of glycolysis in ruminant red blood cells than in red cells of humans and dogs [9]. Glucose fermentation of dietary carbohydrates are short-chain fatty acids, mainly acetate, propionate and butyrate (for review, see [44]). As a consequence of the low dietary absorption of glucose, blood glucose level is slightly lower in weaned ruminants than in monogastric species, and ruminants have somewhat adapted the regulation of their glucose metabolism (for review, see [18]): for example, the major part of circulating glucose originates from hepatic neoglucogenesis from propionate, lactate, glycerol and amino acids, rather than food absorption.…”
Section: Fate Of Glucosesupporting
confidence: 71%
“…These results are in concordance with a lower rate of glycolysis in ruminant red blood cells than in red cells of humans and dogs [9]. Glucose fermentation of dietary carbohydrates are short-chain fatty acids, mainly acetate, propionate and butyrate (for review, see [44]). As a consequence of the low dietary absorption of glucose, blood glucose level is slightly lower in weaned ruminants than in monogastric species, and ruminants have somewhat adapted the regulation of their glucose metabolism (for review, see [18]): for example, the major part of circulating glucose originates from hepatic neoglucogenesis from propionate, lactate, glycerol and amino acids, rather than food absorption.…”
Section: Fate Of Glucosesupporting
confidence: 71%
“…This delays the absorption of amino acids and fatty acids. As a consequence, the postprandial hormonal status is altered, thereby affecting protein metabolism: insulin secretion is lower with milk replacers rich in proteins which do not curdle in the abomasum (for review, see Hocquette and Bauchart, 1999). Furthermore, with a nonclotting diet, we observed an orientation of the muscle tissue towards a more oxidative type and indications of a lower efficiency of amino acids for protein deposition (Ortigues-Marty et al, 2003).…”
Section: Effect Of Nutrient Deliverymentioning
confidence: 90%
“…the conversion of acetyl-CoA into malonyl-CoA). Consequently, any change in insulin secretion or in LCFA supply to the liver modifies the balance of fat within the liver and therefore the supply of fat to peripheral tissues (for review, see Hocquette and Bauchart, 1999). Other studies have shown that oxidation of fatty acids provides ATP needed for gluconeogenesis supporting strong interrelationships between glucose and fatty acid metabolism in the liver (Drackley et al, 2001).…”
Section: Hepatic Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation might be the low efficiency of bovine animals in secreting FA from the liver [41], therefore directing FA preferentially towards the oxidative pathway. The oxidation of both rumenic and oleic acids led mainly to ASP production.…”
Section: Discussionmentioning
confidence: 99%